Acute ischemic stroke in tuberculous meningitis - Guo, Yi-Jia; Gan, Xin-Ling; Zhang, Ru-Yun; Liu, Yong; Wang, Er-Li; Lu, Shui-Hua; Jiang, Hui; Duan, Hong-Fei; Yuan, Zheng-Zhou; Li, Wei-Min (Frontiers in Public Health, 2024)
Background The underlying mechanism for stroke in patients with tuberculous meningitis (TBM) remains unclear. This study aimed to investigate the predictors of acute ischemic stroke (AIS) in TBM and whether AIS mediates the relationship between inflammation markers and functional disability. Methods TBM patients admitted to five hospitals between January 2011 and December 2021 were consecutively observed. Generalized linear mixed model and subgroup analyses were performed to investigate predictors of AIS in patients with and without vascular risk factors (VAFs). Mediation analyses were performed to explore the potential causal chain in which AIS may mediate the relationship between neuroimaging markers of inflammation and 90-day functional outcomes. Results A total of 1,353 patients with TBM were included. The percentage rate of AIS within 30 days after admission was 20.4 (95% CI, 18.2–22.6). A multivariate analysis suggested that age ≥35 years (OR = 1.49; 95% CI, 1.06–2.09; P = 0.019), hypertension (OR = 3.56; 95% CI, 2.42–5.24; P < 0.001), diabetes (OR = 1.78; 95% CI, 1.11–2.86; P = 0.016), smoking (OR = 2.88; 95% CI, 1.68–4.95; P < 0.001), definite TBM (OR = 0.19; 95% CI, 0.06–0.42; P < 0.001), disease severity (OR = 2.11; 95% CI, 1.50–2.90; P = 0.056), meningeal enhancement (OR = 1.66; 95% CI, 1.19–2.31; P = 0.002), and hydrocephalus (OR = 2.98; 95% CI, 1.98–4.49; P < 0.001) were associated with AIS. Subgroup analyses indicated that disease severity (P for interaction = 0.003), tuberculoma (P for interaction = 0.008), and meningeal enhancement (P for interaction < 0.001) were significantly different in patients with and without VAFs. Mediation analyses revealed that the proportion of the association between neuroimaging markers of inflammation and functional disability mediated by AIS was 16.98% (95% CI, 7.82–35.12) for meningeal enhancement and 3.39% (95% CI, 1.22–6.91) for hydrocephalus. Conclusion Neuroimaging markers of inflammation were predictors of AIS in TBM patients. AIS mediates < 20% of the association between inflammation and the functional outcome at 90 days. More attention should be paid to clinical therapies targeting inflammation and hydrocephalus to directly improve functional outcomes.